1995
DOI: 10.1002/pro.5560040914
|View full text |Cite
|
Sign up to set email alerts
|

The activation pathway of procarboxypeptidase B from porcine pancreas: Participation of the active enzyme in the proteolytic processing

Abstract: The activation process of porcine pancreatic procarboxypeptidase B (pro-CPB) has been studied in detail by a number of complementary methodologies, and a description of the molecular events that lead to the generation of active carboxypeptidase B (CPB) has been deduced. The generated CPB participates in the degradation of its own activation segment by excising C-terminal residues from fragments produced by tryptic proteolysis. The trimming action of CPB is, however, not essential for the release of a fully fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
4
17
1
Order By: Relevance
“…The recombinant pro-CPB was fully activated when incubated at 0°C and at 400/1 pro-CPB/trypsin (w/w) ratio. The maturation course for recombinant pro-CPB is identical to that previously reported for the natural form isolated from porcine pancreas (16). A scheme of the proteolytic maturation process is presented in Fig.…”
Section: Figsupporting
confidence: 72%
See 3 more Smart Citations
“…The recombinant pro-CPB was fully activated when incubated at 0°C and at 400/1 pro-CPB/trypsin (w/w) ratio. The maturation course for recombinant pro-CPB is identical to that previously reported for the natural form isolated from porcine pancreas (16). A scheme of the proteolytic maturation process is presented in Fig.…”
Section: Figsupporting
confidence: 72%
“…The supernatant was loaded onto a hydrophobic interaction butyl column and eluted with a decreasing gradient of ammonium sulfate. The zymogen-containing fractions were selected for their activity against BGA after tryptic activation and re-purified by fast protein liquid chromatography on an anion exchange column (TSK-DEAE) as reported previously (16). The correct processing of the different recombinant proteins was confirmed by both automated Edman degradation analysis of its N-terminal sequence and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Folding studies performed in ADA2h showed an extremely fast two-state kinetics [6], suggesting that ADs could assist in the proenzyme folding. Supporting this hypothesis, recombinant expressions of various forms of CPs in the methylotrophic yeast Pichia pastoris have been proved unsuccessful, whereas the proenzyme forms can be produced at high yields.…”
Section: Introductionmentioning
confidence: 98%